A benchmarked vectorial model and flexible software-tool for in-bulk laser processing - Li, Qingfeng; Chambonneau, Maxime; Blothe, Markus; Gross, Herbert; Nolte, Stefan (2021 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2021, 2021)
In-bulk processing of materials by laser radiation has largely evolved over the last decades and still reveals new scientific and industrial potentials. The development of any in-bulk processing application relies on the knowledge of laser propagation and especially the volumetric field distribution near the focus. Many commercial programs can simulate this, but, in order to adapt them, or to develop new methods, one needs to create their own software. Besides, most of the time people also need to measure the actual field distribution near the focus to evaluate their assumptions in the simulation. To help people easily get access to this knowledge, we present our high-precision field distribution measuring method and release our in-house software InFocus [1] , [2] , under the Creative Commons 4.0 License, an open-source license. Our measurements provide 300-nm longitudinal resolution and diffraction limited lateral resolution. The in-house software allows a fast vectorial analysis of the focused volumetric field distribution in the bulk. Lens-induced aberrations are accounted for, together with the spherical aberration provoked by the interface between two materials. The simulations are systematically compared to propagation imaging measurements. As shown in Fig. 1(a) , the experimental results benchmark our model. We also highlight a limitation of this propagation imaging method. As shown in Fig. 1(b) , when laser beam is focused at the exit surface of a 5-mm crystallized silicon (c-Si) sample, the intensity distribution obtained by the propagation imaging methods (b)-i will deviate from the actual intensity distribution (b)-ii due to the significant spherical aberration provoked by the high refractive index mismatch ( n c-Si = 3.5, n air = 1) [3]. However, the measurements in (b)-i are in excellent agreement with the simulations of the imaging procedure (b)-iii.
CRIS-Team Scopus Importer:2023-04-20